Characteristic damage state of symmetric laminates subject to uniaxial monotonic-fatigue loading. (August 2018) - Pakdel, Hamed; Mohammadi, Bijan
Highlights: Experiments show sequential occurrence of matrix cracks and induced delaminations in laminates. Matrix crack density at saturation is shown to change with cracked ply thickness and orientation. Crack density at saturation is identical under static and fatigue loading with different stresses. Crack density at saturation is a characteristic damage state (CDS) independent of loading. CDS can be predicted with an energy based criterion based on energy release rate. Abstract: Experimental and variational investigation of the onset of matrix crack saturation and induced delamination initiation are performed in laminates containing mid-ply matrix cracks. An evolution criterion is developed based on energy release rate to predict the crack density at saturation which is argued to be a characteristic damage state (CDS) independent of loading. A unit cell based analysis is established upon variational principles to derive the stress state and strain energy of [ θ m ( o ) / θ n ( i ) ] s laminates containing mid-ply cracks with or without induced delaminations. Tensile static and fatigue experiments are performed on CFRP specimens with different layups under several maximum stress and stress ratios and optical microscopy is used to detect matrix crack density during experiments. The saturation crack densities of laminates subject to static and fatigue loading with different maximum stress and stress ratios confirm the characteristic damage state (CDS) to be independent of loading as argued in the proposed criterion. Analytical predictions of CDS of different layups are shown to be in accordance with experimental observations.